A new species of Asterocheres (Copepoda, Siphonostomatoida) with a redescription of A. complexus Stock, 1960 and A. sarsi Bandera & Conradi, 2009 - Bandera, Eugenia; Conradi, Mercedes (Zootaxa, 2014)
The present paper reviews the material of three species of Asterocheres Boeck 1859 deposited in four different Zoological European museums as part of the ongoing taxonomical revision of this genus. Asterocheres sarsi Bandera & Conradi 2009, the species described by Sars in 1915 as Ascomyzon latum (Brady 1880) and lately recognized as a distinct species by Bandera and Conradi in 2009 is fully described in this paper from material collected by Sars in Norway in 1915 and deposited in The Natural History Museum of the University of Oslo. Asterocheres complexus Stock, 1960 which has been sometimes confused with A. sarsi is redescribed from material collected by Stock in France in 1959 and deposited in the Zoological Museum of the University of Amsterdam. Furthermore, a new species, previously misidentified as A. suberitis Gieisbrecht 1897, from the Norman`s collection of The Natural History Museum of London, is described as A. eugenioi, new species. These three species, A. complexus, A. eugenioi, and A. sarsi share the general appearance of body thanks to the pointed posterolateral angle of the epimeral area of somite bearing leg 3, sometimes slightly produced into backwardly directed processes, and somite bearing leg 4 largely concealed under somite bearing leg 3.